DDEL-07. A Phase I study examining the feasibility of intermittent convection-enhanced delivery (CED) of MTX110 for the treatment of children with newly diagnosed diffuse midline gliomas (DMGs). (3rd June 2022) - Zacharoulis, Stergios; Szalontay, Luca; CreveCoeur, Travis; Neira, Justin; Higgins, Dominique; Englander, Zachary; Spinazzi, Eleonora; Sethi, Chankrit; Canoll, Peter; Garvin, James; Zylber, Rebecca; Damment, Steve; et al.
Abstract: Histone deacetylase inhibitors have been found preclinically to be among the most active agents against DMGs, however, they are clinically ineffective with systemic delivery due to blood brain barrier limitations and toxicity. Using a repurposed device (implantable subcutaneous pump connected with a catheter directly implanted into the pons/thalamus) we are performing a phase I, standard 3 + 3 dose escalation study to investigate the safety and feasibility of repeated infusions of MTX110 (Midatech Pharma), a water-soluble formulation of panobinostat, via CED. Eligible patents are between 3 and 18 years of age with newly diagnosed DMG following radiation therapy, without hemorrhage or cyst in the tumor, and having intact organ function. Following tumor biopsy and device implantation, patients receive two 48-hour-infusion pulses 7 days apart of MTX110 (30, 60, or 90 mM). The infusion pump is prefilled with MTX110 (and gadolinium for co-infusion to serve as a surrogate for drug distribution) and administered using the wireless N'Vision clinical programmer at a rate of 0.2 mL/hr. Seven patients (30 mM group, n=3 and 60 mM group, n=4) have been treated with the MTX110 infusate. All but one patient had adequate tumor coverage as measured by co-infused gadolinium on MRI. One patient suffered a severe adverse event related to the infusion and tumor anatomy. Four patients had Grade 2 transient neurological deficits related to biopsy (n=1) and the infusion (n=3). In a follow up period of 12-22 months from diagnosis, progression free survival ranges from 8 to 20 months. With one objective response, 3 patients remain alive (2 without progression, both at 12 months, and 1 with progressive disease, at 22 months post diagnosis). Three patients are expected to be treated at 90 mM level. Using MTX110, we demonstrated the safety and feasibility of repeated drug infusion by CED in DMG patients.